Herpes simplex keratitis - an unusual clinical presentation - Arya, SK; Malhotra, C; Bhatia, R; Sood, S (Nepalese Journal of Ophthalmology, 2010)
A case of posterior corneal abscess with extension into the anterior chamber, in the presence of an intact corneal epithelium and clear anterior corneal stroma, occurring in a young patient is described. The patient responded to treatment with systemic and topical acyclovir. The diagnosis of presumed herpes simplex keratitis was made. We report this unusual presentation of ocular herpes manifesting as a posterior corneal and anterior chamber abscess. Keywords: ocular herpes; corneal abscess; acyclovir DOI: 10.3126/nepjoph.v1i2.3689 Nep J Oph 2009;1(2):136-138